Effect of pH value on corrosion of carbon steel under an applied alternating current. Issue 12 (26th October 2015) - Tang, D.‐Z.; Du, Y.‐X.; Lu, M.‐X.; Liang, Y.; Jiang, Z.‐T.; Dong, L.
Abstract : In this work, corrosion behavior of carbon steel under the application of alternating current (AC) was investigated in electrolyte solutions with five different pH levels, from near‐neutral to alkaline condition, through weight loss measurements, potential monitoring techniques, potentiodynamic polarization tests, electrochemical impedance spectroscopy (EIS) tests, and surface examination. It is found that the corrosion rate of carbon steel decreases with increasing pH value toward the alkaline end while increases with increasing AC current density. When the solution pH becomes highly alkaline, say, 12, passivation occurs on carbon steel surfaces, with an enlarging passive region as pH increases. However, it is worth noting that the passive film suffers from mechanical breakdown when the applied AC current density reaches a critical level. Based on these results, an AC corrosion mechanism of carbon steel in near‐neutral and alkaline environment is proposed.